Temperature, saline stress, sowing method and water availability in the germination of bahiagrass seeds - de Souza, Antonio Maricélio Borges; Ferraz, Marcos Vieira; Braga, André Caturelli [UNESP]; da Silveira, Mariana Martins [UNESP]; Queiroz, Gabriel Longuinhos [UNESP]; Campos, Thiago Souza [UNESP]; Pivetta, Kathia Fernandes Lopes [UNESP] (FapUNIFESP (SciELO), 2024)
Bahiagrass (Paspalum notatum Flüggé), native to Brazil, was once widely used in landscaping and is currently more commonly found along roadsides and in large urban areas with old plantings, such as squares, parks, public and industrial areas, among others. Brazil has been developing research into the selection of varieties of this grass, and it is important to know about seed germination in this process and also in commercial multiplication, aiming to form high-quality lawns, quickly and sustainably. Thus, the objective of this research was to evaluate factors that affect the germination of bahiagrass seeds, such as temperature, saline stress, sowing method and water availability in the substrate. Five temperature conditions were studied (room temperature, 25 °C, 30 °C, 20-30 °C, and 25-35 °C); in the salt stress study, five treatments were applied, including a control (absence) and four NaCl concentrations (25, 50, 75, and 100 mM). Two forms of sowing (on and between sand) were also studied, combined with four water contents (25%, 50%, 75%, and 100%) of the water retention capacity in sand. The germination percentage and the germination speed index (GSI) of the seeds were evaluated. The germination of P. notatum seeds was more effective at a temperature of 20-30 °C, in the absence of NaCl, and with a 25% water retention capacity in sand. Sowing in sand, with a water retention capacity of 100%, impairs the germination of bahiagrass seeds.
Temperatura, estresse salino, forma de semeadura e disponibilidade de água na germinação de sementes de grama-batatais
Keywords: grass; Paspalum notatum; Poaceae; salinity; seed technology